The dollmaker - Burton, Mary (Mary T.) (Burton, Mary (Mary T.). Forgotten files, 2023)
Someone with a twisted mind is kidnapping women and altering their faces to resemble real, life-size dolls. Forensic pathologist Tessa McGowan's job to aid the agent leading the case-- even if that agent is her estranged husband. Twelve years ago an unspeakable tragedy destroyed Dakota Sharp's world, and now he has devoted himself to capturing killers-- and cost him Tessa. As the Dollmaker case brings them together, they may just have their second chance. But Tessa may be the Dollmaker's next target ...